Short Communication: In vitro response of papaya (Carica papaya) to plant growth regulators - JAIME A. TEIXEIRA DA SILVA (Smujo International, 2016)
Abstract. Teixeira da Silva JA. 2016. In vitro response of papaya (Carica papaya) to multiple plant growth regulators. Nusantara Bioscience 8: 77-82. The use of plant growth regulators (PGRs) in papaya (Carica papaya L.) tissue culture is essential for tissue and organ culture in vitro. In this study, in a bid to expand the information available on the response to PGRs, a wide range of PGRs, roughly divided into four groups (auxins, cytokinins, alternative PGRs, growth inhibitors, and retardants) was tested. Among them, the auxins 2,4-D, dicamba, and picloram formed most callus (hard and soft). Callus inductions by chitosan and coconut water are novel results for papaya. Shoots only formed in response to BA and TDZ, but TDZ-induced shoots were fascinated and/or hyperhydric. These results provide novel perspectives for papaya researchers who may have recalcitrant genotypes or tissues that are unresponsive in vitro.